L’anti-teoria funzionalista: presupposti, sviluppo ed eredità di una dottrina delle relazioni internazionali - Marinucci, Pierluigi (Studi Politici, 2023)
In this article, an attempt is made to reconstruct the main theoretical steps of the functionalist doctrine, elaborated by David Mitrany since the early 1940s. The main goals of functionalist theory were those of a lasting social peace that could not be reduced to the mere absence of violence. At the same time, by isolating the theoretical frameworks of the functionalist cooperative procedure, its differences with neo-functionalism are noted in comparison.